Multi–criteria evaluation and simulated annealing for delimiting high priority habitats of Alectoris chukar and Phasianus colchicus in Iran - Momeni Dehaghi, I. (Animal Biodiversity and Conservation, 2018)
Habitat degradation and hunting are among the most important causes of population decline for Alectoris chukar and Phasianus colchicus, two of the most threatened game species in the Golestan Province of Iran. Limited data on distribution and location of high–quality habitats for the two species make conservation efforts more difficult in the province. We used multi–criteria evaluation (MCE) as a coarse–filter approach to refine the general distribution areas into habitat suitability maps for the species. We then used these maps as input to simulated annealing as a heuristic algorithm through Marxan in order to prioritize areas for conservation of the two species. To find the optimal solution, we tested various boundary length modifier (BLM) values in the simulated annealing process. Our results showed that the MCE approach was useful to refine general habitat maps. Assessment of the selected reserves confirmed the suitability of the selected areas (mainly neighboring the current reserves) making their management easier and more feasible. The total area of the selected reserves was about 476 km2. As current reserves of the Golestan Province represent only 23 % of the optimal area, further protected areas should be considered to efficiently conserve these two species.